Pengaruh Discount, Influencer Marketing, Dan Kualitas Produk Terhadap Impulse Buying Pada Konsumen E-Commerce Shopee (Studi Pada Karyawan Departemen Overall Drape PT Hogy Indonesia) - Dewi, Oktaviani Isti Kumala; Asral, Asral (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The motivation behind this research stems from the substantial expansion of information technology and e-commerce in Indonesia, which has considerable prospects for the development of the e-commerce sector. In the face of growing competition, it is crucial to comprehend the impact of elements like discounts, influencer marketing, and product quality on impulse buying behavior, particularly on the Shopee platform.The objective of this study is to elucidate the impact of discount, product quality, and influencer marketing on impulsive buying behavior in the context of E-commerce platform Shopee. Additionally, it aims to determine which factor exerts the greatest influence on impulse buying on Shopee. This research falls under the category of quantitative descriptive research. The study was carried out between February and March 2024, with a sample of 93 respondents who were Shopee users employed at the Overall Drape Department of PT Hogy Indonesia. Data gathering is achieved by the dissemination of surveys and conducting literature investigations. The employed analytical techniques encompass validity testing, reliability testing, classical assumption testing of multiple linear regression analysis, and hypothesis testing. The t test findings indicate a calculated t value of 3.098, with a significance level of 0.003. This suggests that the first hypothesis is accepted, demonstrating a positive and substantial effect between discount and impulse buying. The variable of influencer marketing has a computed t value of 4.468 and a significance value of 0.000. This suggests that the second hypothesis is accepted, demonstrating a positive and significant influence between influencer marketing and impulse buying. The t test value for the product quality variable is -1.136, with a significance value of 0.259. This indicates that the third hypothesis is rejected, suggesting that there is no substantial effect between product quality and impulse buying. The analysis indicates that 42.5% of impulse buying may be attributed to the variables of discount, influencer marketing, and product quality. The remaining 57.5% of impulse buying is impacted by additional variables that were not included in the research.